2017
DOI: 10.1039/c6sc04744k
|View full text |Cite
|
Sign up to set email alerts
|

Selective N-terminal functionalization of native peptides and proteins

Abstract: A highly site-selective modification of peptides/proteins with aldehydes or carbohydrates under mild conditions was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 52 publications
1
112
0
Order By: Relevance
“…It is therefore likely that N‐terminal modification will not affect the inherent function of wild‐type proteins or enzymes in most cases . Since an N‐terminal α‐amino group has a lower p K a value than the ϵ‐amino group of the Lys side chain, a reagent targeting the N‐terminal amino acid is expected to be particularly effective for modification of this site . For example, Francis and co‐workers, and other researchers have reported a site‐specific and one‐step N‐terminal α‐amino group modification Scheme using 2‐pyridinecarbaldehyde derivatives …”
Section: Figurementioning
confidence: 99%
“…It is therefore likely that N‐terminal modification will not affect the inherent function of wild‐type proteins or enzymes in most cases . Since an N‐terminal α‐amino group has a lower p K a value than the ϵ‐amino group of the Lys side chain, a reagent targeting the N‐terminal amino acid is expected to be particularly effective for modification of this site . For example, Francis and co‐workers, and other researchers have reported a site‐specific and one‐step N‐terminal α‐amino group modification Scheme using 2‐pyridinecarbaldehyde derivatives …”
Section: Figurementioning
confidence: 99%
“…The methodology is compatible with peptides produced by any method where the linker can be semisynthetically conjugated to a selective amine, preferably the Nterminus 24 . The linker can be further optimized to enhance the biophysical properties of synthetic intermediates.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, the change of a pair of lysine-mutated scFvs in scFv dimer showed different affinity and cytotoxicity, suggesting that the side chain of lysine residue was dominantly reacted; however, there is no critical evidence that only the γ-amino group was reacted. Recently, several specific reactions for N-terminus have been reported [38,39]. Utilization of the reaction for the capping of N-terminus would ensure the homogeneous formation of scF dimers.…”
Section: Discussionmentioning
confidence: 99%